Primary Sjögren syndrome that initially presented with repeated hypergammaglobulinemic purpura after prolonged sitting: A case report. Issue 50 (December 2017) - Zhou, Zhihua; Jiang, Weiqiang; Wang, Ming; Liu, Yongyuan; Zhang, Wei; Huang, Manping; Liang, Donghui
Abstract: Rationale: Purpura is a common dermatologic manifestation in Sjögren syndrome (SS). When a patient presents with sicca symptoms, the diagnosis of SS is not difficult. Patient concerns: Here, we reported a case of a 52-year-old Chinese woman who initially presented with nonpalpable purpura on both lower extremities, and these lesions had developed soon after prolonged sitting. In the past 2 years, she had repeated cutaneous nonpalpable purpura 4 times. She had no sicca symptoms, dry eyes, or dry mouth. Diagnoses: Combining the laboratory findings, Schirmer test, and labial gland biopsy, primary SS was confirmed. Interventions: The patient was placed on a trial of hydroxychloroquine (200 mg once daily). Outcomes: The purpura on both lower extremities had faded at the sixth day after onset and at the third day after hydroxychloroquine treatment. Lessons: These case was not easy to diagnosis primary SS because she had no sicca symptoms. A patient with primary SS who initially presented with recurrent purpura associated with prolonged sitting. Prolonged sitting had been a possible aggravating factor for the cutaneous purpura of this patient with primary SS.